Soft Tissue Tumor - Pangestika, Anindhita; Wisnu R Danu N, Lalu (Jurnal Syntax Fusion, 2021)
Soft tissue tumors are a heterogeneous group of benign and malignant lesions that develop from a variety of nonepithelial, extraskeletal elements, including adipose tissue, smooth and skeletal muscle, tendons, cartilage, fibrous tissue, blood vessels, and lymphatic structures. The writing of this article includes various sources originating from scientific journals and government guidelines and related agencies. Source searches were carried out on online portals for journal publications such as Med Scape Google Scholar (scholar.google.com) and the National Centre for Biotechnology Information/NCBI (ncbi.nlm.nih.gov), with the keyword “Sensoric Nerve Trauma”. Soft tissue tumors (STT) can be benign or malignant, and benign soft tissue tumors are more common than malignant tumors with a ratio of 100: 1. In a study of 93 cases of soft tissue tumors, it was found that the incidence of benign tumors was 75.2% and malignant tumors were 24.8%. Soft tissue tumors are associated with genetic conditions, radiation, chronic lymphedema, environmental carcinogens, and infections.